ANALISIS KEMAMPUAN PEMECAHAN MASALAH LUAS JURING LINGKARAN KELAS VI SDN SAWAH BESAR 01 DENGAN MODEL PROBLEM BASED LEARNING - nurlaily fibrianti; Farida Nursyahidah; Bagus Ardi Saputo; Hamidah Noer (Journal Prakarsa Paedagogia, 2023)
This study contains an analysis of problem-solving abilities on the material of the area of a circular section using a Problem Based Learning model in class VI of SDN Sawah Besar 01, Semarang City. Problem solving abilities are abilities that need to be developed in the 2013 curriculum. Learning models that can be applied to hone problem solving skills include the Problem Based Learning model. The purpose of this research is to analyze problem-solving abilities on the area of circular arc using the Problem Based Learning model. This study used a descriptive qualitative research method with a total of 35 students in class VI A, 20 male students and 15 female students as research samples. The results of this study indicate that 26 out of 35 students in class VI A of 35 students meet the Minimum Mastery Criteria (KKM) with a percentage of 74,28% this shows students can achieve mastery learning with problem solving indicators.